AKUNTABILITAS PENGELOLAAN DANA DESA PADA MASA PANDEMI COVID-19 DALAM THEORY OF PLANNED BEHAVIOR - FRANCO BENONY LIMBA; SHELLA GILBY SAPULATTE; ALFRIN ERNEST MARTHEN USMANY (Fakultas Ekonomi Universitas Islam Indragiri, 2020)
Accountability of government officers in managing Village Funds during the covid-19 pandemic has become a public concern. The aim of this research is to test the factors that influence the intention of the village officers in the Teon Nila Serua (TNS) Distric to be accountable in managing the village’s fund. The samples technique used is the saturated sample, so, all of the population became the sample. The samples used in this study are 118 vilagge officers who have involved in managing at village’s funds during the covid-19 pandemic. The data were collected through the questionnaires and the method used in examining the model and hypothesis was the Partial Least Square (PLS). This research shows that there a positive and significant influence of attitude towards accountability, subjective norms and self efficacy toward the intention to be accountable in managing village’s funds. In addition, SPSS test shows that all of the three determinants are simultaneously have an impact on the intention according to theory of planned behavior.